1969
DOI: 10.12669/pjms.314.7453
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological examination of appendicectomy specimens at a district hospital of Saudi Arabia

Abstract: Background and Objective:Appendicectomy for acute appendicitis is one of the most commonly performed surgical procedures. Acute appendicitis has remained a clinical entity and an ongoing diagnostic challenge. A retrospective study was performed to determine histological diagnosis, demographic data, the rate of perforated appendicitis and negative appendicectomies.Methods:Histopathological records of 480 resected appendices submitted to histopathology department at Arar Central Hospital in the Northern Border P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 10 publications
4
16
2
Order By: Relevance
“…10,14 The acceptable negative appendicitis rate is 10-20%. 8 In this study, the histopathological analysis of 155 cases showed acute appendicitis in 45.8%, while in other studies it was similar with 45.6%, 52% and 30.6%. 6,8,12 The next more common cause of appendicitis in our study was recurrent appendicitis in 21.9%.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…10,14 The acceptable negative appendicitis rate is 10-20%. 8 In this study, the histopathological analysis of 155 cases showed acute appendicitis in 45.8%, while in other studies it was similar with 45.6%, 52% and 30.6%. 6,8,12 The next more common cause of appendicitis in our study was recurrent appendicitis in 21.9%.…”
Section: Discussionsupporting
confidence: 68%
“…8 In this study, the histopathological analysis of 155 cases showed acute appendicitis in 45.8%, while in other studies it was similar with 45.6%, 52% and 30.6%. 6,8,12 The next more common cause of appendicitis in our study was recurrent appendicitis in 21.9%. The incidence of perforated appendicitis in our study was higher 9% compared to others with 1.9%, 2.1% and 2%.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations